Diazotrophic Paenibacillus beijingensis BJ-18 Provides Nitrogen for Plant and Promotes Plant Growth, Nitrogen Uptake and Metabolism - Li, Yongbin; Li, Yunlong; Zhang, Haowei; Wang, Minyang; Chen, Sanfeng (Frontiers in Microbiology, 2019)
Diazotrophic bacteria can reduce N2 into plant-available ammonium (NH4+), promoting plant growth and reducing nitrogen (N) fertilizer requirements. However, there are few systematic studies on the effects of diazotrophic bacteria on biological N2 fixation (BNF) contribution rate and host plant N uptake and metabolism. In this study, the interactions of the diazotrophic Paenibacillus beijingensis BJ-18 with wheat, maize and cucumber were investigated when it was inoculated to these plant seedlings grown in both low N and high N soils, with un-inoculated plants as controls. This study showed that GFP-tagged P. beijingensis BJ-18 colonized inside and outside seedlings, forming rhizospheric and endophytic colonies in roots, stems and leaves. The numbers of this bacterium in the inoculated plants depended on soil N levels. Under low N, inoculation significantly increased shoot dry weight (wheat 86.1%, maize 46.6% and cucumber 103.6%) and root dry weight (wheat 46.0%, maize 47.5% and cucumber 20.3%). The 15N-isotope-enrichment experiment indicated that plant seedlings derived 12.9%-36.4% N from BNF. The transcript levels of nifH in the inoculated plants were 0.75-1.61 folds higher in low N soil than those in high N soil. Inoculation enhanced NH4+ and nitrate (NO3-) uptake from soil especially under low N. The total N in the inoculated plants were increased by 49.1%-92.3% under low N and by 13%-15.5% under high N. Inoculation enhanced activities of glutamine synthetase (GS) and nitrate reductase (NR) in plants, especially under low N. The expression levels of N uptake and N metabolism genes: AMT (ammonium transporter), NRT (nitrate transporter), NiR (nitrite reductase), NR, GS and GOGAT (glutamate synthase) in the inoculated plants grown under low N were up-regulated 1.5-91.9 folds, but they were not obviously changed under high N. Taken together, P. beijingensis BJ-18 was an effective, endophytic and diazotrophic bacterium. This bacterium contributed to plants with fixed N2, promoted plant growth and N uptake, and enhanced gene expression and enzyme activities involved in N uptake and assimilation in plants. However, these positive effects on plants were regulated by soil N status. This study might provide insight into the interactions of plants with beneficial associative and endophytic diazotrophic bacteria.